2017
DOI: 10.4055/cios.2017.9.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Poly-L-Lactic Acid and Poly-L-Lactic Acid/Hydroxyapatite Bioabsorbable Screws for Tibial Fixation in ACL Reconstruction: Clinical and Magnetic Resonance Imaging Results

Abstract: BackgroundThe purpose of this study was to compare the clinical and radiological results of 2 different tibial fixations performed using bioabsorbable screws with added hydroxyapatite (HA) and pure poly-L-lactic acid (PLLA) screws in anterior cruciate ligament (ACL) reconstruction.MethodsA total of 394 patients who underwent arthroscopic ACL reconstruction between March 2009 and June 2012 were retrospectively reviewed. Of those, 172 patients who took the radiological and clinical evaluations at more than 2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In our study, the screw with biocomposite (TCP) showed a 36.83% enlargement of the tibial tunnel, close to studies with addition of HA. 4 , 18 However, in the group with pure PLDL, enlargement of the tibial tunnel (35.24%) was slightly lower than the TCP group, unlike most studies. 4 , 17 , 18 …”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In our study, the screw with biocomposite (TCP) showed a 36.83% enlargement of the tibial tunnel, close to studies with addition of HA. 4 , 18 However, in the group with pure PLDL, enlargement of the tibial tunnel (35.24%) was slightly lower than the TCP group, unlike most studies. 4 , 17 , 18 …”
Section: Discussionmentioning
confidence: 63%
“…It is believed that the addition of biocomposites, such as tricalcium phosphate (TCP) and hydroxyapatite (HA) in PLDL, can accelerate the process of graft incorporation with improved conversion to cancellous bone which reduces acidity during degradation. 17 Lee 4 using MRI, compared the enlargement of the tibial tunnel between PLDL with hydroxyapatite (HA) and pure PLDL screws and found a smaller tibial tunnel enlargement (27.4% x 41.3%), similar to Robinson 18 who also found a smaller tibial tunnel enlargement using CT, 29.9% with the addition of HA to PLDL compared to pure PLDL 46%. In our study, the screw with biocomposite (TCP) showed a 36.83% enlargement of the tibial tunnel, close to studies with addition of HA.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations